Strengthening the reading process in kindergarten children: A classroom experience (2020)
This article describes the results obtained with the implementation of a pedagogical strategy to strengthen the reading process in kindergarten children of the “Promoción Social del Norte” Institute of Bucaramanga, through the implementation of a strategy based on the principles of the Doman method. The research was carried out with a qualitative approach, following the phases of the action research methodology. The participating population corresponds to 21 children who started their basic training and their parents. The information gathering technique used in this research was observation and a pedagogical diary the instrument for recording, a detailed record of all events related to the execution of each of the phases of the method, providing valuable data for the investigation; The results achieved were evaluated through a rubric based on basic learning rights and the standards of reading skills for kindergarten. The results indicate that it is possible to strengthen the reading process in kindergarten children through the use of innovative methods supported by theoretical foundations that recognize the learning potential of kindergarten children and the principles that govern language development in the early years of schooling; in this case, the relevance of the reading bits proposed by the Doman method is reaffirmed.